Theoretical foundations of phenomenography: a critical review. Issue 7 (10th November 2021) - Hajar, Anas
ABSTRACT: Phenomenography is an empirical approach to ascertain the qualitatively different ways in which individuals experience and understand aspects of the world around them. Originating in educational research (Marton, F., & Säljö, R. (1976). On qualitative differences in learning. 1- outcome and process. British Journal of Educational Psychology, 46 (1), 4–11), phenomenography has since been deployed in a range of disciplines, including marketing, nursing and physics. This paper traces the development of traditional phenomenography, together with its ontological and epistemological underpinnings. It also addresses some questions related to the methodological assumptions of phenomenographic research – the most common research methods, characteristics of the sample and the relationship between a phenomenographer and their participants. The fundamental strengths and weaknesses of phenomenography and some issues regarding the validity and reliability of phenomenographic studies are also discussed. By doing this, the paper aims to encourage scholars to consider the possibilities and opportunities offered by taking a phenomenographic approach in their future research.